2017
DOI: 10.1039/c7tc02297b
|View full text |Cite
|
Sign up to set email alerts
|

High color rendering index trichromatic white and red LEDs prepared from silane-functionalized carbon dots

Abstract: White LEDs with high CRI values can be produced by silane-functionalized carbon dots with green and red emission that have potential to be luminescence and encapsulation layers simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…The three silica/CDots composites exhibit similar FT−IR spectra (Figure S5, Supporting Information), indicating their similar chemical compositions. Typically, the absorbances at 3440 and 1659 cm −1 are assigned to the NH and CONH stretching vibration, respectively . The absorbance peak at 1700 cm −1 is ascribed to the stretching vibration of CO.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The three silica/CDots composites exhibit similar FT−IR spectra (Figure S5, Supporting Information), indicating their similar chemical compositions. Typically, the absorbances at 3440 and 1659 cm −1 are assigned to the NH and CONH stretching vibration, respectively . The absorbance peak at 1700 cm −1 is ascribed to the stretching vibration of CO.…”
Section: Resultsmentioning
confidence: 90%
“…The UV–vis spectra, PL excitation, and PL emission spectra are taken along the horizontal and vertical dash lines in the corresponding excitation–emission matrix in Figure a–c are shown in Figure d–f. The absorption spectra of silica/CDots composites show the dominating bands at λ max ≈ 400, 470, and 470 nm for B‐silica/CDots to O‐silica/CDots, respectively, which can be assigned to the n–π* transition of CO . Specifically, the Y‐silica/CDots show absorption at 470 nm and the emission at 568 nm, which is very important in blue LED‐based white LED (WLED) applications.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, as one of tri‐primary colors, the red emissive CDs with QYs over 30% are barely reported . To the best of our knowledge, there are rare reports about polymerizable red emissive CDs …”
Section: Introductionmentioning
confidence: 98%
“…Hence, CDs have become a potential alternative of conventional fluorescent materials for applications in bioimaging, LEDs, energy conversion/storage, lasers, and optical limiters . Furthermore, researchers have prepared multicolor emissive CDs with high quantum yields (QYs) . Nevertheless, it is still a challenge to achieve the uniform dispersion and retain the indigenous properties of CDs in solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al have reported the polysiloxane functionalized orange luminescent carbon quantum dots. Recently, same group have also synthesized red emissive CQDs using silane‐functionalization . And, Ma et al have reported CQDs doped sodium borosilicate gel glasses as a red fluorescent material.…”
Section: Introductionmentioning
confidence: 93%